Cybersecurity in the European Union Resilience and Adaptability in Governance Policy - Christou, George; SpringerLink (Online service) (London : Palgrave Macmillan UK (Imprint), 2016)
Cybercrime affects over 1 million people worldwide a day, and cyber attacks on public institutions and businesses are increasing. This book interrogates the European Union's evolving cybersecurity policies and strategy and argues that while progress is being made, much remains to be done to ensure a secure and resilient cyberspace in the future.
Keywords: European Union; Politics and war; International relations; Political science